Reflecting on Teaching Practice: Adopting Islamic Liberatory Pedagogies within Muslim Institutes of Higher Education in UK (MIHEUK) - Suddahazai, Imran Hussain Khan (Religions, 2023)
The aim of this paper is to discuss the practice of Islamically informed liberatory pedagogical practice within a MIHEUK, through a ‘self-reflective’ dialogue. As the former course leader for Education Studies at the Markfield Institute of Higher Education, the paper examines the derived reflections and experience of the author teaching the BA degree program in Islamic studies with Education and the MA Post-Graduate Degree program in Islamic Education (2019–2022). In contributing to the discussion, the paper adopts a critically reflective interpretivist–hermeneutical methodology, whereby Fazlur Rahman’s double hermeneutical model is utilised to contextualise core educational principles from the Islamic weltanschauung (1982). The paper cites an example exercise study utilised to analyse the adoption of Islamically informed liberatory pedagogical practices. The findings from this exercise reveal that the students’ general ability to critically reflect upon the Islamic educational tradition reflect the influence of the teacher. However, the increased ability of the students to act independently and think critically to challenge the limits to their own potential or understanding of the sources dictating their religiosities and subjectivities is from a place of authenticity, thereby demonstrating the transformative nature of self-realisation as conscientization (critical consciousness) and its realisation of latent potentialities.